Arabidopsis ROCK1 transports UDP-GlcNAc/UDP-GalNAc and regulates ER protein quality control and cytokinin activity - Niemann, Michael C E; Bartrina, Isabel; Ashikov, Angel; Weber, Henriette; Novák, Ondřej; Spíchal, Lukáš; Strnad, Miroslav; Strasser, Richard; Bakker, Hans; Schmülling, Thomas; Werner, Tomáš (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The formation of glycoconjugates depends on nucleotide sugars, which serve as donor substrates for glycosyltransferases in the lumen of Golgi vesicles and the endoplasmic reticulum (ER). Import of nucleotide sugars from the cytosol is an important prerequisite for these reactions and is mediated by nucleotide sugar transporters. Here, we report the identification of REPRESSOR OF CYTOKININ DEFICIENCY 1 (ROCK1, At5g65000) as an ER-localized facilitator of UDP-N-acetylglucosamine (UDP-GlcNAc) and UDP-N-acetylgalactosamine (UDP-GalNAc) transport in Arabidopsis thaliana. Mutant alleles of ROCK1 suppress phenotypes inferred by a reduced concentration of the plant hormone cytokinin. This suppression is caused by the loss of activity of cytokinin-degrading enzymes, cytokinin oxidases/dehydrogenases (CKXs). Cytokinin plays an essential role in regulating shoot apical meristem (SAM) activity and shoot architecture. We show that rock1 enhances SAM activity and organ formation rate, demonstrating an important role of ROCK1 in regulating the cytokinin signal in the meristematic cells through modulating activity of CKX proteins. Intriguingly, genetic and molecular analysis indicated that N-glycosylation of CKX1 was not affected by the lack of ROCK1-mediated supply of UDP-GlcNAc. In contrast, we show that CKX1 stability is regulated in a proteasome-dependent manner and that ROCK1 regulates the CKX1 level. The increased unfolded protein response in rock1 plants and suppression of phenotypes caused by the defective brassinosteroid receptor bri1-9 strongly suggest that the ROCK1 activity is an important part of the ER quality control system, which determines the fate of aberrant proteins in the secretory pathway.
Keywords: transportní proteiny; biologický transport; Phenotype; Uridine Diphosphate N-Acetylgalactosamine; Arabidopsis Proteins; meristém; Endoplasmic Reticulum; uridindifosfát-N-acetylglukosamin; cytokininy; Cytokinins; proteiny huseníčku; Biological Transport; Carrier Proteins; Arabidopsis; fenotyp; endoplazmatické retikulum; Uridine Diphosphate N-Acetylglucosamine; uridindifosfát-N-acetylgalaktosamin; Meristem